Harnessing microalgae as a bioresource for nutraceuticals: advancing bioactive compound exploration and shaping the future of health and functional food innovation - Anjuman Ayub; Farida Rahayu; Aniswatul Khamidah; Sri Satya Antarlina; Kasma Iswari; Khojin Supriyadi; Elya Mufidah; Anjuvan Singh; Chirag Chopra; Atif Khurshid Wani (Discover Applied Sciences)
Abstract Microalgae, which include over 30,000 different species, are an incredibly rich source of nutrients and health-boosting compounds. They have shown impressive health benefits due to their antioxidant, anti-inflammatory, antimicrobial, and anticancer properties, making them valuable for developing medicines, functional foods, and dietary supplements. Advances in technology, such as improved bioreactor systems, genetic engineering, and metabolic fine-tuning, have made it easier to grow microalgae and increase the production of beneficial compounds. Additionally, using microalgae in wastewater treatment and CO2 capture supports environmental and economic sustainability, contributing to a more circular and eco-friendly economy. However, challenges like high production costs and scalability barriers persist. Despite these hurdles, microalgae present a transformative solution to address the growing demand for bioactive compounds and sustainable health interventions. The ongoing research shows their application across industries, including pharmaceuticals, animal husbandry, and aquaculture, paving the way for novel, sustainable nutrition, and health. However, there are still hurdles to overcome. Producing microalgae on a large scale remains costly, and the amount of bioactive compounds produced can vary. Regulatory challenges and the need to increase consumer awareness and acceptance also make it difficult for microalgal products to reach the mainstream market. Despite these issues, ongoing progress in biotechnology, AI-based process optimization, and strain improvement offers promising solutions to make microalgae production more efficient and commercially viable. The growing use of microalgae in pharmaceuticals, health supplements, animal feed, and aquaculture highlights their potential to revolutionize the health and nutrition industries. This review aims to explore the nutritional profile of microalgae, their health benefits, and the technological and market challenges involved, while suggesting future strategies to unlock their full potential in sustainable health and nutrition.